PENGARUH PENGGUNAAN INTERNET BANKING DAN MOBILE BANKING TERHADAP KINERJA KEUANGAN PERBANKAN (STUDI PADA PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA 2016-2020) - Syahputra, Rahmad; Suparno, Suparno (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
This study aims to examine the effect of internet banking and mobile banking on the financial performance of banks listed on the Indonesia Stock Exchange (IDX). The population in this study is all banks listed on the Indonesia Stock Exchange in 2016-2020. This sampling technique uses purposive sampling with the company's criteria stating the number of transactions through internet banking and mobile banking during 2016-2020. There are 7 banks that become the research sample. The data collection technique used in this research is documentation. This research is a quantitative research with multiple linear regression analysis method. The results showed that internet banking has a significant influence on the financial performance of banks. Meanwhile, mobile banking has no effect on banking financial performance.